PERAN ASOSIASI ASPAKUSA MAKMUR BOYOLALI DALAM PEMBERDAYAAN PETANI - Muna, Wardatul; Gayatri, Siwi; Satmoko, Sriroso (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 1 (2020): Vol. 14 No. 1, 2020DO - 10.24843/SOCA.2020.v14.i01.p02, 2020)
The vegetable farmers need an effort to increase their ability so they can produce the optimal quantiity and quality vegetables for meet an increasing demand. Aspakusa Makmur Boyolali  is an agribusssines association that seeks to self farmer so that market demand can be met.This reasearch aims was to analyze the role of the Aspakusa Makmur Boyolali Association in to improve self relience anoy farmers. The role of the Association of Aspakusa Makmur Boyolali in empowerment can be seen through empowerment strategies. The research was conducted on  February 2th - March 4th 2019 in Aspakusa Makmur Boyolali Association located in Teras Village, Boyolali Regency. The method used in this study was survey with 35 members of the association. Analytical methodin used descriptive analysis conducted bay multiple linear regression analysis. The results of this study were 1) the role of the Aspakusa Makmur Boyolali Association in empowering its members and self relience were categorized as high, 2) there was significant influence betwen relo of associantion in empowering strategies toward self relience anoy the farmers. 3) Partially the variables that influence self relief are counseling and mentoring strategies, and strategies for access to science and technology.